2010
DOI: 10.1108/09604521011073759
|View full text |Cite
|
Sign up to set email alerts
|

Updating service operations

Abstract: PurposeThe purpose of this paper was to develop a customer‐oriented systems approach to updating a service operation. The approach will allow managers to gather information, make changes in service delivery and then assess the effects of these changes.Design/methodology/approachA survey was developed and administered at intervals in the same service setting; data from these survey results were used to illustrate the proposed systems‐based approach. Data from the open‐ended survey question were analyzed using c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 41 publications
0
6
0
Order By: Relevance
“…A systems approach requires a model that captures all major components of the learning process and their inter-relationships. The systems perspective outperforms a piecemeal approach to improving reliability which can generate counter-productive measures that may waste time, effort and money (Sulek and Hensley, 2010;Testa and Snipe, 2006). The service management literature contains several systems models of quality and reliability (Sulek and Hensley, 2010;Lusch, Vargo and O'Brien, 2007;Stewart, 2003, Chase andBowen, 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A systems approach requires a model that captures all major components of the learning process and their inter-relationships. The systems perspective outperforms a piecemeal approach to improving reliability which can generate counter-productive measures that may waste time, effort and money (Sulek and Hensley, 2010;Testa and Snipe, 2006). The service management literature contains several systems models of quality and reliability (Sulek and Hensley, 2010;Lusch, Vargo and O'Brien, 2007;Stewart, 2003, Chase andBowen, 1991).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The systems perspective outperforms a piecemeal approach to improving reliability which can generate counter-productive measures that may waste time, effort and money (Sulek and Hensley, 2010;Testa and Snipe, 2006). The service management literature contains several systems models of quality and reliability (Sulek and Hensley, 2010;Lusch, Vargo and O'Brien, 2007;Stewart, 2003, Chase andBowen, 1991). This paper will utilize the 3T model devised by Stewart (2003) because its emphasis on component inter-relationships makes it well suited to the learning process.…”
Section: Literature Reviewmentioning
confidence: 99%
“…In addition, Madu (1999, p. 696) has suggested that “managers adopt a systemic view in reviewing an unreliable system”. In a similar fashion, some service management researchers have underscored the need for a systems approach to service quality (Lusch et al , 2007; Sulek and Hensley, 2010; Stewart, 2003; Chase and Bowen, 1991). Since reliability is intertwined with quality and has even been defined by Sun et al (2008, p. 152) as “quality over time”, a system wide view of service reliability should be further developed in the service literature.…”
Section: Service Reliability Frameworkmentioning
confidence: 99%
“…Some experiential studies show that getting a good quality of service from the food and beverage (F&B) department of a hotel is important for many guests (Armstrong et al, 1997;Crick & Spencer, 2011;Cronin & Taylor, 1992a;Getty & Thompson, 1994;Lam & Zhang, 1998;Parasuraman. et al, 1988a;Sulek & Hensley, 2010;Zeithaml & Bitner, 2003). Researchers have defined service quality in relation to the concept of consumer-perceived quality, which is based solely on the perspective of customers.…”
Section: Introductionmentioning
confidence: 99%